2008
DOI: 10.1088/0967-3334/29/7/010
|View full text |Cite
|
Sign up to set email alerts
|

Reduced short-term complexity of heart rate and blood pressure dynamics in patients with diabetes mellitus type 1: multiscale entropy analysis

Abstract: Multiscale entropy (MSE) analysis provides information about complexity on various time scales. The aim of this study was to test whether MSE is able to detect autonomic dysregulation in young patients with diabetes mellitus (DM). We analyzed heart rate (HR) oscillations, systolic (SBP) and diastolic blood pressure (DBP) signals in 14 patients with DM type 1 and 14 age- and sex-matched healthy controls. SampEn values (scales 1-10) and linear measures were computed. HR: among the linear measures of heart rate v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 25 publications
3
42
0
Order By: Relevance
“…Nonlinear measures encompass a heterogeneous group of statistics, several of which quantify the entropy or complexity of the signal. Multiscale sample entropy is one such statistic that has been used to distinguish patients with cardiovascular pathologies from healthy subjects (10,29,30) and is predictive of mortality in trauma and heart failure patients (17,21,22,26).…”
mentioning
confidence: 99%
“…Nonlinear measures encompass a heterogeneous group of statistics, several of which quantify the entropy or complexity of the signal. Multiscale sample entropy is one such statistic that has been used to distinguish patients with cardiovascular pathologies from healthy subjects (10,29,30) and is predictive of mortality in trauma and heart failure patients (17,21,22,26).…”
mentioning
confidence: 99%
“…In addition, the MC-ApEn analysis between left fingertip PPG pulse amplitudes with other different physiological signals of ECG R-R intervals demonstrated similar results. Costa et al and Trunkvalterova et al have demonstrated that the small-scale MSE of heart rate variability-reflecting autonomic function-was decreased in diabetes, and similarly, the large-scale MSE of pulse transit times-a surrogate of peripheral arteriosclerosis-was also lower in diabetes [24,25]. The MSE index of unilateral finger PPG pulse amplitudes may reflect peripheral vascular health of the tested upper extremity side.…”
Section: Discussionmentioning
confidence: 96%
“…However, the influence of handgrip strength on any time scales MSE or RMSE was not remarkable in individuals without diabetes and those with poorly controlled diabetes. Several physiological signals such as sleep electroencephalographic wave [26], electromyographic signals [27], body temperature [28], intracranial pressure [29], pulse rate [12], and blood pressure [15] have been used for MSE analysis to mainly evaluate autonomic nervous dysfunction, cardiovascular disease, treatment effect, and disease prognosis. Trunkvalterova et al revealed that the MSE of blood pressures and pulse rate at scale factor = 3 in patients with type 1 diabetes were significantly lower than those in the unaffected controls [15].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the nonlinearity of large-time scales MSE are much related to autonomic sympathetic activity and established cardiovascular disease [14]. Previous reports have shown that the MSE of heart rate, blood pressure, and pulse wave velocity might be more sensitive than the linear analysis of HRV parameters to detect subclinical vascular abnormalities in diabetes [15,16].…”
Section: Introductionmentioning
confidence: 99%